2010
DOI: 10.1073/pnas.1000674107
|View full text |Cite
|
Sign up to set email alerts
|

Cortical and subcortical interactions during action reprogramming and their related white matter pathways

Abstract: The right inferior frontal gyrus (rIFG) and the presupplementary motor area (pre-SMA) have been identified with cognitive controlthe top-down influence on other brain areas when nonroutine behavior is required. It has been argued that they "inhibit" habitual motor responses when environmental changes mean a different response should be made. However, whether such "inhibition" can be equated with inhibitory physiological interactions has been unclear, as has the areas' relationship with each other and the anato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

31
266
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 239 publications
(305 citation statements)
references
References 24 publications
31
266
4
Order By: Relevance
“…Whereas previous evidence for a relationship between pMFC activity and PES (Gehring et al, 1993;Garavan et al, 2002;Kerns et al, 2004;Debener et al, 2005;di Pellegrino et al, 2007) did not speak to the specific role of the motor system in this adjustment, our finding of reduced post-error motor activity is in line with recent evidence (Marco-Pallares et al, 2008;King et al, 2010) suggesting motor inhibition as a mechanism underlying PES. Consistent with this, transcranial magnetic stimulation (TMS) studies have recently demonstrated that the pre-SMA can modulate M1 activity in conflicting situations and thus influence corticospinal excitability (Mars et al, 2009;Neubert et al, 2010). This corroborates our result showing that pMFC activity predicts the strengths of motor activity following errors, i.e., stronger pMFC activity leads to less motor activity in the post-error trial.…”
Section: Discussionsupporting
confidence: 81%
“…Whereas previous evidence for a relationship between pMFC activity and PES (Gehring et al, 1993;Garavan et al, 2002;Kerns et al, 2004;Debener et al, 2005;di Pellegrino et al, 2007) did not speak to the specific role of the motor system in this adjustment, our finding of reduced post-error motor activity is in line with recent evidence (Marco-Pallares et al, 2008;King et al, 2010) suggesting motor inhibition as a mechanism underlying PES. Consistent with this, transcranial magnetic stimulation (TMS) studies have recently demonstrated that the pre-SMA can modulate M1 activity in conflicting situations and thus influence corticospinal excitability (Mars et al, 2009;Neubert et al, 2010). This corroborates our result showing that pMFC activity predicts the strengths of motor activity following errors, i.e., stronger pMFC activity leads to less motor activity in the post-error trial.…”
Section: Discussionsupporting
confidence: 81%
“…3B). Recent paired-coil TMS studies demonstrated effective connectivity between pre-SMA and M1 via corticocortical and cortical-subcortical routes (Mars et al, 2009;Neubert et al, 2010), but these effects were specifically dependent on motor tasks requiring action reprogramming and for this reason are not at variance with the present results obtained at rest.…”
Section: Topographic Specificity Of Pas-induced Plasticity In the Smacontrasting
confidence: 57%
“…Additionally, little is known about potential role of other areas of the frontal lobe that might be involved in these post-error adjustments. Neubert et al (2010) reported evidences of the contribution of the inferior frontal gyrus as well as other non-primary areas of the motor system such the pre-supplementary motor area (pre-SMA) and the premotor cortex of the ipsilateral hemisphere in task switching and motor inhibition that might be also be implicated in the modulation of the excitability of the corticospinal system. Furthermore, other areas outside the frontal lobe, such as the intra-parietal sulcus implicated in sensory visual feedback and integration (Gre´a et al, 2002;Wolynski et al, 2009), might project to the DLPFC in the frontal lobe and ultimately to premotor and motor systems.…”
Section: Discussionmentioning
confidence: 99%